A new cell-free therapeutic strategy for liver regeneration: Human placental mesenchymal stem cell-derived extracellular vesicles. (October 2022) - Li, Ting; Fu, Yu; Guo, Zeyi; Zhu, Honglei; Liao, Hangyu; Niu, Xiaoge; Zhou, Lin; Fu, Shunjun; Li, Yang; Li, Shao; Wang, Lujia; Zheng, Yizhou; et al.
Mesenchymal stem cells (MSCs) have potential role in organ regeneration therapy. Previous work indicating that MSCs confer protection against liver disease. Here, we aimed to determine the potential application in liver regeneration of human placenta-derived MSCs extracellular vesicles (hPMSCs-EVs) via experimental hepatectomy. hPMSCs-EVs were administered intravenously 24 h before 70% partial hepatectomy, the specific composition of hPMSCs-EVs was identified by sequencing and validated by the quantitative polymerase chain reaction, including circ-RBM23. The role of circ-RBM23 in L02 cell was evaluated and it was found that circ-RBM23 knockdown inhibited L02 cell proliferation both in vitro and in vivo. The competing endogenous RNA function of circ-RBM23 was evaluated by the RNA immunoprecipitation assay and found that circ-RBM23 shares miRNA response elements with RRM2. Overexpressed circ-RBM23 bound competitively to miR-139-5p, preventing the miRNA-mediated degradation of RRM2, activating the expression of eIF4G and AKT/mTOR, and facilitating liver regeneration. These results indicate that hPMSCs-EVs prevent hepatic dysfunction and improve liver regeneration in vivo and hepatocytes proliferation in vitro, potentially via circ-RBM23 delivery.